LOCAL GOVERNMENT AND COMMUNITY LEADERS' PERSPECTIVES ON CHILD HEALTH AND MORTALITY AND INEQUITY ISSUES IN RURAL EASTERN INDONESIA. Issue 1 (29th April 2016) - Pardosi, Jerico Franciscus; Parr, Nick; Muhidin, Salut
Summary: Since 2001 a decentralization policy has increased the responsibility placed on local government for improving child health in Indonesia. This paper explores local government and community leaders' perspectives on child health in a rural district in Indonesia, using a qualitative approach. Focus group discussions were held in May 2013. The issues probed relate to health personnel skills and motivation, service availability, the influence of traditional beliefs, and health care and gender inequity. The participants identify weak leadership, inefficient health management and inadequate child health budgets as important issues. The lack of health staff in rural areas is seen as the reason for promoting the use of traditional birth attendants. Midwifery graduates and village midwives are perceived as lacking motivation to work in rural areas. Some local traditions are seen as detrimental to child health. Husbands provide little support to their wives. These results highlight the need for a harmonization and alignment of the efforts of local government agencies and local community leaders to address child health care and gender inequity issues.